Answer:
a= -1
b= -9
c=9
d=3
e=3
f=2
![g=\frac32](https://img.qammunity.org/2021/formulas/mathematics/high-school/3rp5g0x7sb3gpfmtpjuum2u12fcbydfr1g.png)
Explanation:
Rule of sign:
- (-)×(+)=(-), (-)÷(+)=(-)
- (+)×(-)=(-) , (+)÷(-)=(-)
- (+)×(+)=(+), (+)÷(+)=+
- (-)×(-)=(+), (-)÷(-)=(+)
Given that,
![(3x)/(2x-6)+(9)/(6-2x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ytzx9hpu1i4zaq7xf3ic581oh7g4nhu87z.png)
We can rewrite 6-2x as 2x-6, taking (-1) as common factor of (6-2x)
![=(3x)/((2x-6))+(9)/(-1(2x-6))](https://img.qammunity.org/2021/formulas/mathematics/high-school/hc7eqeaob5oo8hmyqckh0vmx3upb5s8moa.png)
So, a= -1
![\frac9{-1}=-9](https://img.qammunity.org/2021/formulas/mathematics/high-school/khu94y0h38kt6fpf9btse93mpei1328c5h.png)
![=(3x)/((2x-6))+(-9)/((2x-6))](https://img.qammunity.org/2021/formulas/mathematics/high-school/p43882zkcgrrttyaip3pas8jwru1mtbdr0.png)
So, b= -9
The L.C.M of (2x-6) and (2x-6) is (2x-6)
and (2x-6)÷(2x-6)=1
![=(1 * 3x+1* (-9))/((2x-6))](https://img.qammunity.org/2021/formulas/mathematics/high-school/j0y1dnr2docgd5tegrzxy7eunnhti51kcr.png)
![=(( 3x-9))/((2x-6))](https://img.qammunity.org/2021/formulas/mathematics/high-school/nugxb5v9k31nw7yutw6fa6qia8uybbx930.png)
∴c= 9
(3x-9) has a common factor 3 and (2x-6) has a common factor 2.
(3x-9)=3(x-3)
(2x-6)=2(x-3)
![=(3(x-3))/(2(x-3))](https://img.qammunity.org/2021/formulas/mathematics/high-school/rkleavp58wnuj6zt9z3lfhhkb74aa80a8e.png)
∴d=3, e=3 and f=2
Since the denominator and numerator are the product of two polynomial. So, if there is any common element, then can cancel the common factor.
Here the common factor is (x-3). So cancel out (x-3).
![=\frac32](https://img.qammunity.org/2021/formulas/mathematics/high-school/ghqizx3zprqu13z9g14vhcq0lv2xu7zu12.png)
![\therefore g=\frac32](https://img.qammunity.org/2021/formulas/mathematics/high-school/ddghm9arqz1ak6de8dmnrtpxcpthnygrh4.png)